(untitled) (Stamford Journal of Pharmaceutical Sciences, 2009)
The ethanol leaf extracts of four medicinal plants named Hibiscus mutabilis, Leucas aspera, Ixora coccinea and Polyalthia longifolia were examined for their possible regulatory effect on nitric oxide (NO) levels using sodium nitroprusside as a NO donor in vitro. Most of the extracts tested demonstrated direct scavenging of NO and exhibited significant activity and the potency of scavenging activity was in the following order: Leucas aspera > Ixora coccinea > Hibiscus mutabilis> Polyalthia longifolia. All the evaluated extracts exhibited a dose-dependent NO scavenging activity. The ethanolic leaf extract of Leucas aspera showed the greatest NO scavenging effect of 80.50% at 320 Î¼g/ml with IC50 value of 94.15 Î¼g/ml as compared to the positive control ascorbic acid where 74.56 % scavenging was observed at similar concentration with IC50 value of 62.48 Î¼g/mL. The maximum NO scavenging of Ixora coccinea, Hibiscus mutabilis and Polyalthia longifolia were 79.65 %, 78.60% and 70.67 % with IC50 values of 43.72 Î¼g/ml, 147.64 Î¼g/ml and 167.08 Î¼g/ml respectively. The present results suggest that these plants might be potent and novel therapeutic agents for scavenging of NO and the regulation of pathological conditions caused by excessive generation of NO and its oxidation product. Keywords: Nitric oxide scavenging activity, Antioxidant study, Active nitrogen species. Â doi:10.3329/sjps.v1i1.1809 S. J. Pharm. Sci. 1(1&2): 57-62